Identification of QTLs for aphid (Melanaphis sacchari) resistance in sorghum (Sorghum bicolor) based on BSA-seq and analysis of candidate genes - Junli Du; Kunliang Zou; Qi Shen; Yang Liu; Minghui Guan; Tonghan Wang; Degong Wu; Lihua Wang; Yongfei Wang; Jieqin Li (BMC Plant Biology)
Abstract Aphid infestation significantly reduces the yield and forage quality of sorghum, underscoring the urgent need to identify and develop aphid-resistant sorghum varieties. Marker-assisted selection (MAS) remains one of the most effective strategies for enhancing aphid resistance in sorghum. In this study, an F2 segregating population derived from a cross between the aphid-resistant variety IS23514 and the susceptible variety IS23992 was employed to map aphid resistance genes using bulked segregant analysis based on whole-genome resequencing (BSA-seq) and Insertion-Deletion (InDel) marker analysis. Genetic analysis indicated that aphid resistance in sorghum is governed by a dominant gene. A quantitative trait locus (QTL) associated with aphid resistance (qMsa-6) was identified within a 124 kb region on chromosome 6. Candidate gene prediction and protein domain analysis within this region revealed ten previously uncharacterized genes, seven of which possess NB-ARC domains. Subsequent qPCR analysis revealed that the SbiRTX2783.06G018400 gene is the most likely candidate conferring aphid resistance. This study offers critical molecular insights into the mechanisms underlying aphid resistance in sorghum and identifies key candidate genes for future aphid-resistant breeding programs.